From lack of luteal phase to hypothalamic-pituitary-ovarian dysfunction - В. А. Заболотнов; В. И. Шатило; А. М. Рыбалка; А. В. Куприяненко (Publishing House TRILIST, 2018)
The article presents a systematic review of the main pathogenetic mechanisms of the onset and development of insufficiency of the luteal phase (ILF) and its association with hypothalamic-pituitary-ovarian dysfunction. The characteristics of clinical variants of the course of this pathology and its consequences for the reproductive health of women are given. The list of modern methods of ILF diagnosis and brief characteristics of diagnostic studies necessary for correct diagnosis according to current standards and protocols are presented. The review of modern methods of treatment of ILF aimed at correcting the deficit of progesterone, the elimination of hyperprolactinemia and leveling the effects of chronic stress on the body is presented.